Trace-element fractionation in Hadean mantle generated by melt segregation from a magma ocean. - Caro, G; Bourdon, B; Wood, B; Corgne, A (2005)
Calculations of the energetics of terrestrial accretion indicate that the Earth was extensively molten in its early history. Examination of early Archaean rocks from West Greenland (3.6-3.8 Gyr old) using short-lived 146Sm-142Nd chronometry indicates that an episode of mantle differentiation took place close to the end of accretion (4.46 +/- 0.11 Gyr ago). This has produced a chemically depleted mantle with an Sm/Nd ratio higher than the chondritic value. In contrast, application of 176Lu-176Hf systematics to 3.6-3.8-Gyr-old zircons from West Greenland indicates derivation from a mantle source with a chondritic Lu/Hf ratio. Although an early Sm/Nd fractionation could be explained by basaltic crust formation, magma ocean crystallization or formation of continental crust, the absence of coeval Lu/Hf fractionation is in sharp contrast with the well-known covariant behaviour of Sm/Nd and Lu/Hf ratios in crustal formation processes. Here we show using mineral-melt partitioning data for high-pressure mantle minerals that the observed Nd and Hf signatures could have been produced by segregation of melt from a crystallizing magma ocean at upper-mantle pressures early in Earth's history. This residual melt would have risen buoyantly and ultimately formed the earliest terrestrial protocrust.